Multiomics analysis of rheumatoid arthritis yields sequence variants that have large effects on risk of the seropositive subset. Issue 8 (25th April 2022) - Saevarsdottir, Saedis; Stefansdottir, Lilja; Sulem, Patrick; Thorleifsson, Gudmar; Ferkingstad, Egil; Rutsdottir, Gudrun; Glintborg, Bente; Westerlind, Helga; Grondal, Gerdur; Loft, Isabella C; Sorensen, Signe Bek; Lie, Benedicte A; et al.
Abstract : Objectives: To find causal genes for rheumatoid arthritis (RA) and its seropositive (RF and/or ACPA positive) and seronegative subsets. Methods: We performed a genome-wide association study (GWAS) of 31 313 RA cases (68% seropositive) and ~1 million controls from Northwestern Europe. We searched for causal genes outside the HLA-locus through effect on coding, mRNA expression in several tissues and/or levels of plasma proteins (SomaScan) and did network analysis (Qiagen). Results: We found 25 sequence variants for RA overall, 33 for seropositive and 2 for seronegative RA, altogether 37 sequence variants at 34 non-HLA loci, of which 15 are novel. Genomic, transcriptomic and proteomic analysis of these yielded 25 causal genes in seropositive RA and additional two overall. Most encode proteins in the network of interferon-alpha/beta and IL-12/23 that signal through the JAK/STAT-pathway. Highlighting those with largest effect on seropositive RA, a rare missense variant in STAT4 (rs140675301-A) that is independent of reported non-coding STAT4 -variants, increases the risk of seropositive RA 2.27-fold (p=2.1×10 −9 ), more than the rs2476601-A missense variant in PTPN22 (OR=1.59, p=1.3×10 −160 ). STAT4 rs140675301-A replaces hydrophilic glutamic acid with hydrophobic valine (Glu128Val) in a conserved, surface-exposed loop. A stop-mutation (rs76428106-C) in FLT3 increases seropositive RA risk (OR=1.35, p=6.6×10 −11 ). Independent missense variants in TYK2 (rs34536443-C, rs12720356-C, rs35018800-A, latter two novel) associate with decreased risk of seropositive RA (ORs=0.63–0.87, p=10 −9 –10 −27 ) and decreased plasma levels of interferon-alpha/beta receptor 1 that signals through TYK2/JAK1/STAT4. Conclusion: Sequence variants pointing to causal genes in the JAK/STAT pathway have largest effect on seropositive RA, while associations with seronegative RA remain scarce.